Epidemiological characteristics and forecasting incidence for patients with breast cancer in Shantou, Southern China: 2006–2017. (16th March 2021) - Lin, Huang; Shi, Lei; Zhang, Jiachi; Zhang, Jinchan; Zhang, Chichen
Abstract: This study aimed to explore the epidemiological characteristics of breast cancer and establish an Exponential Smoothing (ETS) and Autoregressive Integrated Moving Average (ARIMA) models to predict the development of incidence in Shantou. This study has a large sample size, strong representativeness, and wide‐ranging and comprehensive medical insurance information, which can fill the gaps in basic epidemiological research on breast cancer in Shantou. Successful completion of this study is a helpful tool to understand the epidemiology of Guangdong Province and Southern China. This study also provides data and scientific references for the government and future research on breast cancer prevention and control. This retrospective study was conducted to describe the epidemic intensity, epidemic distribution, and epidemic trend of breast cancer in Shantou, Guangdong Province, from 2006 to 2017, gathered from the Shantou's Medical Security Bureau covers the whole districts of Shantou. ETS and ARIMA models were used to describe the regional distribution, time distribution, and population distribution of breast cancer in Shantou. Moreover, based on the ARIMA model and ETS model, the incidence trend of breast cancer was predicted during 2018–2022. This study included 5, 681 breast cancer patients, majority of whom were aged 50–59 years. The male‐to‐female ratio of the breast cancer patients was about 1:107 (the same ratio of the insured population was 1:1). Female patients accounted for 98.61% of the total insured population. The incidence and mortality rates of female breast cancer were 16.42/100, 000 and 0.66/100, 000, respectively. Based on the ARIMA model or ARIMA and ETS model, a gradually decreasing trend in the incidence of breast cancer is expected in the future. Comparing the performances of the ARIMA model and ETS model, ARIMA (4, 0, 1) (0, 1, 0) model had a lower the root mean squared error and the mean absolute percentage error than ETS (M, N) model. This population‐based retrospective study showed that the high‐risk age for the age‐specific incidence of female breast cancer was 50–55 years. It is recommended that healthcare administration should strengthen program awareness and education regarding breast cancer prevention and control. It is also possible that feasibility of extrapolating the current methodology to other future studies or broader populations in which the cancer registry data are not available. Abstract : This is the first population‐based retrospective study of breast cancer in Shantou, Guangdong Province of Southern China in the past 10 years. The result of the age‐specific incidence of female breast cancer indicated that the high‐risk age was from 50 to 55 years. It is recommended that the health administration strengthen the publicity and education regarding the prevention and control of breast cancer.